LGG-20. MOLECULARLY-DEFINED DIFFUSE LEPTOMENINGEAL GLIONEURONAL TUMOR (DLGNT) COMPRISES TWO SUBGROUPS WITH DISTINCT CLINICAL AND GENETIC FEATURES. Issue 2 (22nd June 2018) - Deng, Maximilian Y; Sahm, Felix; Sill, Martin; Chiang, Jason; Capper, David; Milde, Till; Ebinger, Martin; Schuhmann, Martin; Schittenhelm, Jens; Monoranu, Camelia-Maria; Korshunov, Andrey; Ellison, David; et al.
Abstract: Diffuse leptomeningeal glioneuronal tumors (DLGNT) represent a rare CNS neoplasm included in the latest WHO classification update from 2016. The wide spectrum of histological and radiological features can make this enigmatic tumor entity difficult to diagnose. In recent years, large-scale genomic and epigenomic analyses have provided insight into key genetic alterations in pediatric brain tumors. Through genome-wide DNA methylation screening of >25, 000 tumors, we discovered a distinct class comprising 31 tumors, mostly diagnosed as DLGNTs. Copy number profiles derived from the methylation arrays revealed unifying characteristics, including loss of chromosomal arm 1p in 100% of cases. Furthermore, this molecular DLGNT class could be subdivided into two subgroups (DLGNT-pediatric and DLGNT-adult), with all DLGNT-adult additionally displaying gain of chromosomal arm 1q. Co-deletion of 1p/19q was frequently observed in both subgroups, especially in DLGNT-pediatric cases. Both subgroups also displayed recurrent genetic alterations leading to an aberrant MAPK/ERK pathway, with KIAA1549:BRAF fusion being the most frequent event. Other alterations included fusions of NTRK1/2/3 and TRIM33:RAF1. Age at diagnosis was significantly lower (median 5 vs 14 years, p<0.005) and clinical course less aggressive, in the DLGNT-pediatric group (5-yr OS 100%, vs 50% in DLGNT-adult). Our study proposes an additional molecular layer to the current histopathological classification of DLGNT, of particular use for cases not displaying typical morphological or radiological characteristics. Recurrent 1p deletion and MAPK/ERK pathway activation represent diagnostic and therapeutic biomarkers, laying the foundation for future clinical trials with e.g. MEK inhibitors that may improve the clinical outcome of patients with DLGNT.